Pendampingan Usaha Nasi Kuning Syauqi Berbasis Inovasi Produk dan Adaptasi Digital - Nora Listiana; Ferdinan Chong; Thiaga Rama Pramesya; Zidan Muhamad Ghalib (Eastasouth Institute, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector play a strategic role in supporting local economies but face challenges related to business competition, limited product innovation, and inadequate digital marketing. This Community Service Program aims to enhance the competitiveness of Nasi Kuning Syauqi MSME through product innovation assistance, service quality improvement, and digital adaptation. A participatory mentoring approach was applied through stages of observation, socialization, training, implementation, and monitoring–evaluation. The results indicate improvements in business management awareness, menu variation, customer service quality, and the adoption of digital marketing strategies. This program contributes to MSME sustainability and the strengthening of the local community-based economy.